The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/1529-0131(200109)44:9<2193::aid-art373>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide, a novel diterpenoid triepoxide fromTripterygium wilfordii Hook. f., suppresses the production and gene expression of pro-matrix metalloproteinases 1 and 3 and augments those of tissue inhibitors of metalloproteinases 1 and 2 in human synovial fibroblasts

Abstract: Objective Various extracts of the Chinese herbal remedy Tripterygium wilfordii Hook. f. (TWHF) have been reported to be therapeutically efficacious in rheumatoid arthritis (RA) in China, but their mechanism of action remains unclear. We investigated the effect of triptolide, a diterpenoid triepoxide from TWHF, on the production of pro–matrix metalloproteinase 1 (proMMP‐1; or procollagenase 1 or pro–interstitial collagenase 1), proMMP‐3 (or prostromelysin 1), tissue inhibitors of metalloproteinases (TIMPs), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 27 publications
3
68
0
Order By: Relevance
“…Previous studies showed that triptolide inhibited transcriptional activation through NFkB [28] and suppressed TNFa production by LPS-stimulated macrophages [23] and IL-2 production by PHA-activated T cells. [28] Our results extend these observations by showing inhibition of multiple inflammatory mediators in staphylococcal exotoxin-activated PBMC at both transcriptional and protein level.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies showed that triptolide inhibited transcriptional activation through NFkB [28] and suppressed TNFa production by LPS-stimulated macrophages [23] and IL-2 production by PHA-activated T cells. [28] Our results extend these observations by showing inhibition of multiple inflammatory mediators in staphylococcal exotoxin-activated PBMC at both transcriptional and protein level.…”
Section: Discussionmentioning
confidence: 93%
“…[22] In human synovial fibroblasts, triptolide suppresses the production and expression of prometalloproteinases 1 and 3 and inhibits the expression of COX-2 and IL-1-induced PGE 2 production. [23] Triptolide also inhibits vascular endothelial cell growth factor expression in phorbol 12-myristate 13-acetate (PMA)-activated endothelial cells [24] and attenuates the expression of IL-6, IL-8, and cell adhesion molecule ICAM-1 by PMA-stimulated human bronchial epithelial cells. [25] The effects of triptolide on other cell types include the inhibition of the expression of C3, CD40, and B7H in TNFa-activated human proximal tubular epithelial cells [26] and suppression of LPS-induced TNFa, IL1b, and nitric oxide production by microglial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of PGE 2 production was due to suppression of COX-2 . COX-1 expression was not affected (Lin et al, 2001a). As with the extracts, the inhibitory effects of 1 on PGE 2 production varied depending on the cell line studied .…”
Section: Proinflammatory Enzymes-nitric Oxide Synthase (Nos) Catalyzementioning
confidence: 88%
“…Similarly, triptolide (1) suppressed expression of COX-2 and the precursor forms of MMP-1 and -3, and inhibited production of PGE 2 and NO and activity of lipoxygenase Lin et al, 2001a;Zhou et al, 2003). The inhibition of PGE 2 production was due to suppression of COX-2 .…”
Section: Proinflammatory Enzymes-nitric Oxide Synthase (Nos) Catalyzementioning
confidence: 99%
See 1 more Smart Citation